Mechanical Models for Comparative Analysis of Failure Characteristics and Groundwater Inrush of Coal Seam Floors - Chunbo Zhao; Wencheng Song (Applied Sciences, 2022)
Mining activities conducted above aquifers run the risk of groundwater outburst through fractured floor strata. However, the failure mechanism of the seam floor and the variability in its stability with varying dips remain unclear. Considering the influence of excavation-induced pressure, hydraulic pressure and strata dip, two kinds of analytical models were proposed in this study, which mainly included the hydraulic mechanical model and the key stratum model. These models were applied to comparatively investigate the failure characteristics and inrush risk of horizontal and inclined floors, and then confirmed by numerical simulation. The theoretical calculations reveal that the vertical failure ranges of horizontal and inclined floor strata exhibit approximate “inverted saddle” shapes along the inclination, and have the characteristics of symmetrical distribution and “lower-large/upper-small”, respectively, which is generally consistent with the simulated and measured observations. The theoretical maximum depths of damage within horizontal and inclined floor strata are roughly 12 m and 15 m, slightly lower than the result of numerical simulation. Compared with the remaining horizontal layer, the zone close to the lower boundary of the inclined key strata beneath the goaf incurs the most damage, which corresponds well to the distribution of vertical disturbance ranges. Therefore, the theoretical risk of groundwater outburst from the inclined floor after coal extraction is relatively higher than that from the horizontal floor. The mechanical models established in this study could elucidate the mechanism inducing floor failure and water inrush above a confined aquifer, and thus provide valuable insights for the risk assessment of water-related disasters in underground engineering.